Quantum dot labeling of mesenchymal stem cells - Muller-Borer, Barbara J.; Collins, Maria C.; Gunst, Philip R.; Cascio, Wayne E.; Kypson, Alan P. (East Carolina University, 2007)
Background: Mesenchymal stem cells (MSCs) are multipotent cells with the potential to differentiate into bone, cartilage, fat and muscle cells and are being investigated for their utility in cell-based transplantation therapy. Yet, adequate methods to track transplanted MSCs in vivo are limited, precluding functional studies. Quantum Dots (QDs) offer an alternative to organic dyes and fluorescent proteins to label and track cells in vitro and in vivo. These nanoparticles are resistant to chemical and metabolic degradation, demonstrating long term photostability. Here, we investigate the cytotoxic effects of in vitro QD labeling on MSC proliferation and differentiation and use as a cell label in a cardiomyocyte co-culture. Results: A dose-response to QDs in rat bone marrow MSCs was assessed in Control (no-QDs), Low concentration (LC, 5 nmol/L) and High concentration (HC, 20 nmol/L) groups. QD yield and retention, MSC survival, proinflammatory cytokines, proliferation and DNA damage were evaluated in MSCs, 24 -120 hrs post QD labeling. In addition, functional integration of QD labeled MSCs in an in vitro cardiomyocyte co-culture was assessed. A dose-dependent effect was measured with increased yield in HC vs. LC labeled MSCs (93 ± 3% vs. 50% ± 15%, p < 0.05), with a larger number of QD aggregates per cell in HC vs. LC MSCs at each time point (p < 0.05). At 24 hrs >90% of QD labeled cells were viable in all groups, however, at 120 hrs increased apoptosis was measured in HC vs. Control MSCs (7.2% ± 2.7% vs. 0.5% ± 0.4%, p < 0.05). MCP-1 and IL-6 levels doubled in HC MSCs when measured 24 hrs after QD labeling. No change in MSC proliferation or DNA damage was observed in QD labeled MSCs at 24, 72 and 120 hrs post labeling. Finally, in a cardiomyocyte co-culture QD labeled MSCs were easy to locate and formed functional cell-to-cell couplings, assessed by dye diffusion. Conclusion: Fluorescent QDs label MSC effectively in an in vitro co-culture model. QDs are easy to use, show a high yield and survival rate with minimal cytotoxic effects. Dose-dependent effects suggest limiting MSC QD exposure. Originally published Journal of Nanobiotechnology, Vol. 5, No. 9, Nov. 2007
Keywords: Mesenchymal stem cells; Quantum dots; Transplantation therapy